Pembuatan Biodiesel Dari Biji Saga (Adhenantera Pavonina) Dengan Katalis Padat H-Zeolit - James Becker; Syaiful Bahri; Syamsu Herman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Transesterification reaction is a reaction between the oil (triglyceride) with alcohol to produce methyl esters. One of commercial product is biodiesel. The production of biodieselfrom vegetable oils, especially seed oil saga is still very limited, it is necessary to develop a vegetable oil-based biodiesel. In this research, the manufacture of biodiesel bytransesterification reaction using natural zeolite catalysts are activated to H-Zeolite, with a variation of the molar ratio of reactants (1: 3, 1: 6 and 1: 9) and the number of H-zeolitecatalyst (6%, 8% and 10%) with a fixed variable is the reaction temperature 60 ° C, the reaction time of 200 minutes and the stirring speed of 200 rpm. From the test results showthat the molar ratio transesterification and the amount of catalyst affects the reaction rate toachieve equilibrium of the reaction. The best operating conditions obtained in this study isthe molar ratio of 1: 9 and the amount of catalyst 8% which resulted in a conversion reaction of 86.44%. Characteristics of biodiesel produced in this study meets the standards of commercial biodiesel with kinematic viscosity of 5.15 cp, specific gravity (40 ° C) 0.853 and saponification numbers were 0.49 mg KOH / g sample.Keywords : Biodiesel, H-zeolite, Oil, Transesterification.